Customer satisfaction on islamic banking among students at Universiti Malaysia Kelantan City Campus - Ibrahim, Nur Faika; Yahaya, Norainadia; Mohamad Husin, Nur Diana; Mohd Anuar, Norbaitul Aisyah (2015)
The purpose of this study is to determine the customer satisfaction on islamic banking at Universiti Malaysia Kelantan (UMK) City Campus. The aims are to: (a)to determine the effect of religion towards of customer satisfaction on islamic banking (b) to examine the knowledge factors towads customer satisfaction on islamic banking (c) to determine the effect of service quality towards customer satisfaction on islamic banking. A self-administrated questionnaire was distributed to the respondent among UMK student. Correlation analysis was use to identify which factor from religion, knowledge and service quality that effect the customer satisfaction on islamic banking at UMK City Campus. The correlation model suggested that service quality was influence the customer satisfaction follow by knowledge factor and religion. Islamic banking should focus on the element of service quality and improve the knowledge of their staff in order to satisfy their customer